The effects of a pre-season conditioning program and a season of competition on selected physical fitness measures of women intercollegiate basketball players - Palmer, Anita M. (My University, 1983)
This study measured the effects of a pre-season conditioning program and a season of competition on 6 elements of physical fitness. Cardio-vascular endurance, flexibility, muscular strength and endurance of right and left legs and shoulders, percent body fat, and weight were analyzed through 22 different tests. The tests were administered to 9 Ss a t 3 different times during the season. Trial 1. was given before the pre-season conditioning program, trial 2 was done at the end of the pre-season conditioning program, and Trial 3 was administered at the end of the regular season. One-way ANOVA with repeated measures revealed significant differences, p<.05, for 5 tests from trial 1 to Trial 2: 12-minute run (cardiovascular endurance), sit and reach (flexibility ) , left shoulder extension (strength), and right shoulder flexion and extension (endurance). Significant differences, p < .05, were found for 9 tests from Trial 1 to Trial 3: 12-minute run, sit and reach, shoulder extension (flexibility), right and left leg flexion (strength), left shoulder flexion and extension (strength), right leg flexion (endurance), and left leg extension (endurance). Significant differences, p < .05, were found for 2 tests from Trial 2 to Dial 3: left shoulder extension (strength), and right leg flexion (endurance).
Keywords: Physical fitness for women; Women basketball players